Quality of Nursing Work Life and Nursing Job Performance in Medan, Indonesia - Mula Tarigan; Dani Syahfitri; Siti Khadijah Nasution (Caring: Indonesian Journal of Nursing Science, 2026)
Nursing Quality of Work Life (QNWL) and nursing job performance are important variables for nurses in functioning within nursing organizations. However, empirical evidence examining the relationship between these variables remains scarce in North Sumatra Province, particularly in Medan. This study aimed to assess the relationship between QNWL and nursing job performance at Chairuddin Panusunan Lubis Hospital, Indonesia. This correlational study design involved a total sample of 62 nurses working in inpatient units. The instruments used were the QNWL and nursing work performance questionnaire. The frequency distribution, percentage, and Pearson correlation test were used for data analysis. The findings showed that QNWL and nursing job performance were predominantly in the moderate category. There was a significant and positive relationship between QNWL and nursing job performance (p < 0.001 and r = 0.670), indicating that higher QNWL is associated with better nursing performance. Therefore, maintaining and improving QNWL is essential to enhance nursing job performance, enabling nurses in hospital settings to deliver high-quality care and achieve optimal and safe patient outcomes.  Keyword: Nursing Work Life, Job Performance, Work Environment, Hospital